ANALISIS FAKTOR KEPUTUSAN GENERASI Z MELAKUKAN WAKAF TUNAI - Nasution, Anriza Witi; Marliyah, Marliyah; Siregar, Pani Akhiruddin (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2023)
The purpose of this study was to determine the decision-forming factors of generation Z in Medan in conducting cash waqf. Quantitative methods are used to find the main factors that shape the decision of generation Z in Medan in conducting cash waqf through analysis tools, namely factor analysis to process data from questionnaires distributed to respondents. The selected respondents are generation Z who are active college students. The selection of respondents was carried out using a random sampling method. The results of the study show that the first factors that shape the decision of generation Z in Medan to carry out cash waqf are cash waqf literacy, trust in waqf institutions, and methods of payment. Religiosity is the second factor that shapes the Z generation's decision to make cash waqf in Medan